Prenatal diagnosis and pregnancy outcomes in fetuses with ventriculomegaly - Yue, Fagui; Yang, Xiao; Liu, Ning; Liu, Ruizhi; Zhang, Hongguo (Frontiers in Medicine, 2024)
Objective Genetic etiology plays a critical role in fetal ventriculomegaly (VM). However, the studies on chromosomal copy number variants (CNVs) in fetal VM are limited. This study aimed to investigate the chromosomal CNVs in fetuses with mild to moderate VM, and explore its genotype-phenotype correlation. Methods A total of 242 fetuses with mild to moderate VM detected by prenatal ultrasound were enrolled in our study from October 2018 to October 2022. All cases underwent chromosomal microarray analysis (CMA) and G-banding simultaneously. All VM cases were classified different subgroups according to the maternal age, severity, VM distribution and presence/absence of other ultrasound abnormalities. The pregnancy outcomes and health conditions after birth were followed up. We also performed a pooled analysis regarding likely pathogenic and pathogenic CNVs (LP/P CNVs) for VM. Results The detection rate of chromosomal abnormalities by karyotyping was 9.1% (22/242), whereas it was 16.5% (40/242) when CMA was conducted (P < 0.05). The total detection rate of chromosomal abnormalities by karyotyping and CMA was 21.1% (51/242). A 12.0% incremental yield of CMA over karyotyping was observed. The detection rate of total genetic variants in fetuses with bilateral VM was significantly higher than in fetuses with unilateral VM (30.0% vs. 16.7%, P = 0.017). No significant differences were discovered between isolated VM and non-isolated VM, or between mild and moderate VM, or between advanced maternal age (AMA) and non-AMA (all P > 0.05). 28 fetuses with VM were terminated and 214 fetuses were delivered: one presented developmental delay and one presented congenital heart disease. The VM cases with both positive CMA and karyotypic results had a higher rate of termination of pregnancy than those with either a positive CMA or karyotypic result, or both negative testing results (P < 0.001). Conclusion The combination of CMA and karyotyping should be adopted to improve the positive detection rate of chromosomal abnormalities for VM. The total genetic abnormalities detected using both techniques would affect the final pregnancy outcomes. LP/P CNVs at 16p11.2, 17p13, and 22q11.21 were identified as the top three chromosomal hotspots associated with VM, which would enable genetic counselors to provide more precise genetic counseling for VM pregnancies.